They shoot horses don't they? - Winkler, Irwin; Chartoff, Robert; Pollack, Sydney 1934-2008; Fonda, Jane 1937-; Sarrazin, Michael 1940-2011; York, Susannah 1939-2011 (MGM DVD, 2004)
In the midst of the Depression, an entire generation sought out the dance marathon as a means of survival. Gig Young won an Oscar for Best Supporting Actor as the contest promoter
DVD format. - Recorded in Dolby digital mono. - Letterboxed (2.25:1) format. - Originally released as a motion picture in 1969. - From the novel by Horace McCoy. - Includes original theatrical trailer
Jane Fonda, Michael Sarrazin, Susannah York, Gig Young, Bonnie Bedelia, Red Buttons
Director of photography, Philip H. Lathrop ; editor, Fredric Steinkamp ; music, John Green
Keywords: Dance marathons / United States / Drama; Depressions / 1929 / United States / Drama; Alltag, Brauchtum; United States / Social life and customs / 1918-1945 / Drama; USA